2021
DOI: 10.1002/pat.5558
|View full text |Cite
|
Sign up to set email alerts
|

High density interfaces enhanced microwave absorption in multifunctional carbon nanotubes‐glass fiber‐epoxy composites

Abstract: In this work, we fabricated and systematically investigated the mechanical and microwave absorption properties of multi-walled carbon nanotube (MWCNT)-glass fiber (GF)-epoxy composites. The composites showed high electromagnetic (EM) wave absorption performance in a wide frequency range. The maximum reflection loss of the composites can reach to À48 dB at 24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Eqs. 2-4 utilize these S parameters to determine the reflectance rate (R), absorption rate (A), and transmittance rate (T) (Zhao et al, 2022):…”
Section: Electromagnetic Shieldingmentioning
confidence: 99%
“…Eqs. 2-4 utilize these S parameters to determine the reflectance rate (R), absorption rate (A), and transmittance rate (T) (Zhao et al, 2022):…”
Section: Electromagnetic Shieldingmentioning
confidence: 99%
“…9,10 Carbon nanotubes have exotic physicochemical properties, 11 such as unique metallic or semiconductor electrical conductivity, 12 high mechanical strength, 13 hydrogen storage capacity, 14 adsorption capacity 15 and strong microwave absorption. [16][17][18] The CNTs were first discovered in the early 1990s, and immediately attracted great attention from the physical, chemical and material science communities. 19 At present, the multi-walled carbon nanotubes (MWCNTs) have cost advantages, and are gradually taking over the market of traditional carbon black as reinforcing agents and conductive agents.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the best reflection loss of −60 dB with a −10 dB range of 5.6 GHz could be obtained in an absorber with a triple-layered structure composed of GF-CNTs/epoxy with different CNT contents and GF-CNTs@Ni/epoxy. Zhao, R. et al [33] fabricated and systematically investigated the mechanical and microwave absorption properties of MWCNTs-GF-epoxy composites. The maximum reflection loss of the composites can reach −48 dB at 24.5 GHz.…”
Section: Introductionmentioning
confidence: 99%